2019
DOI: 10.3390/ma12183035
|View full text |Cite
|
Sign up to set email alerts
|

Gray Correlation Analysis and Prediction on Permanent Deformation of Subgrade Filled with Construction and Demolition Materials

Abstract: Construction and demolition (C&D) materials obtained from the demolition of buildings are proven to be qualified and sustainable subgrade fillers. The permanent deformation response of subgrade C&D materials under different moisture contents, degrees of compaction, deviator stresses, and confining pressures was revealed by carrying out dynamic triaxial texts. Then, using a four-factor and three-level orthogonal test and by calculating the Gray correlation degree of each factor, the influence degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In recent years, with the development of society, people's demand for spiritual life is increasing, the incidence of mental illness is also increasing year by year, and the incidence is mostly concentrated in big cities [ 11 13 ]. Modern medicine has a huge amount of complex data; in many cases, it is difficult to achieve a reasonable allocation of resources, which puts forward an urgent demand for the artificial intelligence of modern medicine and also brings great pressure to the development of the medical industry [ 14 16 ]. Compared with other kinds of diseases, the medical data of mental diseases may have more complex data records, which consumes a lot of medical human resources.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of society, people's demand for spiritual life is increasing, the incidence of mental illness is also increasing year by year, and the incidence is mostly concentrated in big cities [ 11 13 ]. Modern medicine has a huge amount of complex data; in many cases, it is difficult to achieve a reasonable allocation of resources, which puts forward an urgent demand for the artificial intelligence of modern medicine and also brings great pressure to the development of the medical industry [ 14 16 ]. Compared with other kinds of diseases, the medical data of mental diseases may have more complex data records, which consumes a lot of medical human resources.…”
Section: Introductionmentioning
confidence: 99%
“…The serviceability of railway tracks is strongly associated with the dynamic stability of unbound granular layers atop weaker layers of the subgrades, of which the critical dynamic stress ( σ cri ) and accumulative plastic/permanent stain ( ε p ) are primary indicators regarding the dynamic stability of unbound granular materials (UGMs) [ 1 , 2 , 3 , 4 , 5 , 6 ]. Subgrades of railways accumulate permanent settlement under dynamic traffic loading, and excessive accumulative surface settlement typically causes problems, such as vehicle turbulence in transition sections [ 7 , 8 ], uneven settlement [ 9 , 10 , 11 ], and lateral expansion of embankment shoulders [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subgrades of railways accumulate permanent settlement under dynamic traffic loading, and excessive accumulative surface settlement typically causes problems, such as vehicle turbulence in transition sections [ 7 , 8 ], uneven settlement [ 9 , 10 , 11 ], and lateral expansion of embankment shoulders [ 12 , 13 , 14 ]. One of the most effective ways to control the accumulative deformation of subgrades is maintaining the traffic-induced dynamic stress to be less than a critical value (i.e., the σ cri ), under which the development rate of ε p gradually decreases and can ultimately cease with an increase in the dynamic loading cycles [ 5 , 15 , 16 ]. Furthermore, the rapid development of high-speed transport and heavy-haul freight demands the subgrades beneath track structures must satisfy strict requirements on accumulative permanent settlements [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zhang et al [ 18 ] analyzed the physical and chemical properties of CDW (construction and demolition waste) materials for expressways, studied the construction technology of the CDW subgrade, and performed a series of tests. Zhang et al [ 19 ] revealed the permanent deformation response of subgrade construction and demolition materials under different water content, compaction, deviator stress, and confining pressure through a dynamic triaxial test. Chen et al [ 20 ] evaluated the feasibility of using cement waste as a filling material for loess roadbeds.…”
Section: Introductionmentioning
confidence: 99%